2012
DOI: 10.2298/vsp1209799i
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate: Predictor of cardiovascular risk

Abstract: nem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These recommendations point out the significance of resting heart rate as an independent predictor of cardiovascular morbidity and mortality in patients with arterial hypertension. [21].…”
Section: Heart Rate and Cardiovascular Mortalitymentioning
confidence: 99%
“…These recommendations point out the significance of resting heart rate as an independent predictor of cardiovascular morbidity and mortality in patients with arterial hypertension. [21].…”
Section: Heart Rate and Cardiovascular Mortalitymentioning
confidence: 99%
“…[ 117 , 118 ] Lots of studies have demonstrated that the heart rate is a major independent cardiovascular risk factor for adverse prognosis. [ 119 ] Reduction of heart rate is the main effect of ivabradine and protects the myocardium against ventricular dysfunction induced by tachycardia. These effects can improve endothelial function, modulate immune cells and enhance a long-term adaptation in calcium handling.…”
Section: Treatmentsmentioning
confidence: 99%